Characterization of Spatial Distribution of Electrolyte in Molten Carbonate Fuel Cell Cathodes. Issue 6 (25th March 2018) - Wejrzanowski, Tomasz; Gluch, Jürgen; Ibrahim, Samih Haj; Cwieka, Karol; Milewski, Jarosław; Zschech, Ehrenfried
Abstract : High‐resolution computed X‐ray tomography (XCT) is applied in this study to characterize the microstructure of Molten Carbonate Fuel Cell (MCFC) cathodes after operation, where a "virgin cathode" formed by porous nickel has been in situ oxidized and infiltrated by liquid electrolyte. This technique extends state‐of‐the art methodology to characterize pores such as porosity analysis using Mercury porosimetry. XCT enables 3D imaging of the internal structure of the electrodes including all components present at the cathode side, particularly NiO, pores, and electrolyte. The quantitative 3D microstructure analysis based on high‐resolution XCT provides topological information for each component and their mutual spatial distribution, which is significant for the enhancement of the MCFC performance. In particular, volume fraction, specific surface area, continuity of each phase, as well as the Triple Phase Boundary (TPB) density are calculated from the experimental data. The results indicate that superior properties of the multi‐modal pore sized cathode, used in this study, can be attributed to the formation of three self‐interpenetrating networks of pathways for the transport of gasses, electrons, as well as ions throughout pores, NiO, and electrolyte, respectively. Abstract : Multi‐modal pore size distributions in the cathode improves Molten Carbonate Fuel Cell performance. The positive effect is caused by the formation of larger pores. High‐resolution X‐ray tomography is applied to reveal the microstructure of the MCFC cathode after operation (oxidized and filled with electrolyte).